Exploring Reproductive Health Education Needs in Infertile Women in Iran: A Qualitative Study - Khakbazan, Zohreh (J Prev Med Public Health, 2020)
OBJECTIVES: An inadequate understanding of infertility can affect individuals’ self-efficacy and ability to perform self-care; thus, reproductive health education is an important part of infertility treatment. The present qualitative study aimed to explore the experiences and educational needs of infertile women with regard to reproductive health. METHODS: In this qualitative study, we utilized a content analysis approach. Purposive sampling was performed to ensure maximum diversity. In total, 23 individual interviews were conducted with 20 Iranian women with infertility and 3 key informants between July 2018 and February 2019 in northern Iran. Data were collected through in-depth, semi-structured interviews. Data analysis was performed using a conventional content analysis approach. RESULTS: Reproductive health education needs were identified by analyzing interview data from 4 main categories: familiarity with the fertility process and preparation for pregnancy, recognition of infertility and expectations around seeking treatment, recognition of preventive actions associated with reproductive health, and correction of false beliefs. Recognizing the causes of infertility and understanding the different approaches to infertility treatment are among the most important educational needs of infertile women. The potential for neglect of health-related issues due to concerns about fertility and the maternal experience necessitates education about preventive measures for cervical cancer, breast cancer, and sexually transmitted infections. Correcting misconceptions, including those related to contraceptives and traditional medicine, can also help promote reproductive health. CONCLUSIONS: In infertile women, the educational needs associated with reproductive health are multifaceted. Satisfying these needs can help achieve optimal treatment results and promote reproductive health.